1968
DOI: 10.1172/jci105712
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of thyroxine distribution in man

Abstract: A group of 13 normal subjects were evaluated for their extrathyroidal thyroxine distribution. The method employed the measurement of the acute plasma disappearance of a thyroxine-'311 tracer and its concomitant uptake into the liver and forearm. The analysis of these prameters allowed the theoretical construction of a four compartmental mathematical model system comprised of the plasma, extracellular fluid, hepatic, and extrahepatic thyroxine pools. The results of this analysis revealed that the exchange of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…On the other hand, only one-fourth of the extrathyroidal T. pool was in the intracellular compartment. Therefore, these results were consistent with the suggestion by previous studies that Ts is predominantly an intracellular hormone (7,28), although the cellular distribution of T2 was relatively smaller than anticipated in previous studies (28,34).…”
Section: 'supporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, only one-fourth of the extrathyroidal T. pool was in the intracellular compartment. Therefore, these results were consistent with the suggestion by previous studies that Ts is predominantly an intracellular hormone (7,28), although the cellular distribution of T2 was relatively smaller than anticipated in previous studies (28,34).…”
Section: 'supporting
confidence: 93%
“…The findings suggested that the return of T4 to systemic circulation was more significant than in the case of T8. It has been previously postulated that about 15% of the entire extrathyroidal Ts pool would appear to be extracellular (28,34). In the present paper, in which both intracellular distribution and total distribution volume of Ts were estimated by the three-compartmental analysis, approximately 60% of the extrathyroidal Ts pool was in the intracellular compartment.…”
Section: 'mentioning
confidence: 52%
“…The tracer for W. E., H. R., and C. S. had been dialyzed to remove contaminating "I-as suggested by Nicoloff and Dowling (7). The residual "'I-was less than 0.2%o as determined on the day of injection by paper electrophoresis in glycine-acetate buffer, pH 8.6.…”
Section: Methodsmentioning
confidence: 99%
“…DPH (Dilantin, Parke, Davis & Co., Detroit, Mich.) was administered orally on the following various schedules: W. E. and H. R. received 6.7 mg/kg and 4.7 mg/kg, respectively, on days 12 through 26; J. G., 2.4 mg/kg on days 10 through 17 and 4.9 mg/kg on days 17 through 24; D. S., 7.0 mg/kg on days 10 through 18; and C. S., 5.3 mg/kg on days 10 through 25. These dosages correspond to the usual therapeutic range of 300-400 mg/day.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently described several techniques for the measurement of the compartmental distribution and deiodination of extrathyroidal thyroxine in normal human subjects (5). These techniques allow the quantitative estimation of the thyroxine distribution in the plasma, extracellular fluid, hepatic, and extrahepatic tissue compartments, as well as a semiquantitative estimation of the relative deiodinating activities of the hepatic vs. the extrahepatic compartments.…”
mentioning
confidence: 99%